Comparative study of family 2 GPCRs in Fugu rubripes - Cardoso, João CR (2014)
In this study, members of family 2 GPCRs, one of the largest families of receptors in vertebrates, were isolated and characterized in the genome of the Japanese pufferfish, Fugu rubripes, and compared with the orthologous genes in other vertebrates. Phylogenetic analysis carried out with all vertebrate family 2 GPCR members indicated that CALR/CGRPR and CRF are the most divergent receptor group within this family and that the remaining members appear to originate from a common ancestral gene precursor.